Facet effect on CO2 adsorption, dissociation and hydrogenation over Fe catalysts: Insight from DFT. (July 2018) - Wang, Haozhi; Nie, Xiaowa; Chen, Yonggang; Guo, Xinwen; Song, Chunshan
Graphical abstract: Highlights: Energetically favorable adsorption configurations of CO2 and H2 on Fe(100), (110), (111) and (211) are identified. The (111) and (211) facets exhibit superior ability towards reactant activation. CO2 adsorption stability significantly decreases when surface H* gest to high coverage. Fe facet impacts the formation of key intermediates and preferred pathways. The (111) facet seems to be the promising candidate for CO2 conversion. Abstract: Periodic density functional theory (DFT) calculations were performed to investigate the facet effect on CO2 adsorption, dissociation and hydrogenation over Fe catalysts. The energetically most stable configurations of CO2 and H2 adsorption over different Fe facets were identified from which we observed that CO2 adsorption on Fe(211) and Fe(111) is much stronger than other facets, indicating more sufficient activation of CO2 on these two surfaces. CO2 adsorption stability was found to be impacted by the surface coverage of H* on these Fe facets, showing that when surface H* coverage exceeds to certain percentage, CO2 adsorption is largely weakened whilst the electrons transfer from the Fe surface to CO2 becomes decreased. These results suggest that an appropriate H2 -CO2 co-adsorption equilibrium is important for effective activation of reactants. Based on the examination of CO2 dissociation and hydrogenation on these Fe facets, the Fe(111) is potentially the most active facet for CO2 conversion due to a lower barrier for HCOO* formation via CO2 hydrogenation while this facet is also catalytically more active for activating CO2 . Fe(110) and Fe(100) exhibit more facile ability to dissociate CO2 to CO* while kinetically competitive formation of CO* and HCOO* was observed over Fe(211). The present work demonstrates that the facet of Fe catalysts can impact the molecular adsorption, activation and conversion path in CO2 hydrogenation and thus can alter the product selectivity.